Navigating UNCRPD concluding observations on Article 27: policy exploration on disability inclusive employment - S. L. Ashalatha; Satish Kumar; B. R. Santosh; B. K. Ravindra (Cogent Social Sciences, 2024)
To explore critical concerns and recommendations outlined by the United Nations committee in its Concluding Observations on Article 27, focusing on addressing challenges related to disability employment. The study aims to identify and accumulate insights of the UN committee informing directions towards framing effective strategies for enhancing inclusive employment opportunities for PWDs. The study design involves qualitative exploration of the relevance between the concerns and recommendations under Article 27, based on concluding observations across eleven state parties from five continents. The sample nations selected are the top-developed countries according to the Human Development Index. Content analysis is employed to analyze the compliance status of state parties in the concluding observations made by the UN Committee of CRPD. The findings systematically categorize 21 causative factors, consequential effects and proposed policy interventions across legislative, administrative, judicial, civil society and employer-centric obligations. The study concludes that while the UNCRPD recommendations hold legal legitimacy, their lack of specificity necessitates more targeted policy intervention and future research, prompting investigations into developing more tailored and nuanced policy interventions that effectively address disability employment challenges.